2012
DOI: 10.1371/journal.pone.0047714
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Early Parkinson's Disease with Multi-Modal MR Imaging

Abstract: BackgroundIn recent years, neuroimaging has been increasingly used as an objective method for the diagnosis of Parkinson's disease (PD). Most previous studies were based on invasive imaging modalities or on a single modality which was not an ideal diagnostic tool. In this study, we developed a non-invasive technology intended for use in the diagnosis of early PD by integrating the advantages of various modals.Materials and MethodsNineteen early PD patients and twenty-seven normal volunteers participated in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 53 publications
3
97
0
Order By: Relevance
“…This finding is consistent with a previous study, which reported a higher connectivity degree in the PCC and precuneus in PD patients compared with healthy controls [37]. Additionally, increased regional homogeneity and gray matter volume have been reported in the PCC and precuneus in PD patients compared with healthy controls [38,39]. However, the exact mechanism underlying the increased FCD is still unclear.…”
Section: Increased Short-and Long-range Fcds In Pd Patientssupporting
confidence: 92%
“…This finding is consistent with a previous study, which reported a higher connectivity degree in the PCC and precuneus in PD patients compared with healthy controls [37]. Additionally, increased regional homogeneity and gray matter volume have been reported in the PCC and precuneus in PD patients compared with healthy controls [38,39]. However, the exact mechanism underlying the increased FCD is still unclear.…”
Section: Increased Short-and Long-range Fcds In Pd Patientssupporting
confidence: 92%
“…When we estimate a candidate PD to be positive or negative with ReHo alteration, the specificity of the ReHo approach should be considered. The specificity may be improved by multi-modal imaging (Long et al, 2012) or incorporation in multi-modal classifiers (Joshi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the various application of fMRI, regional homogeneity (ReHo), a kind of processed fMRI signal, has been utilized in automatic discrimination of early PD (Long et al, 2012). Generally, ReHo analyses were applied to the restingstate fMRI (RS-fMRI) data which records the blood oxygen level-dependent (BOLD) signals while participants lie still inside an MRI scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Since an overwhelming amount of literature exits (Mueller et al, 2005; Ohtsuka et al, 2013) that relate neurodegenerative impairments to morphological abnormalities in the brain, MRI studies that reveal the structural abnormalities of the brain, or PET and SPECT studies that reveal the functional abnormalities of the brain have been widely used. Furthermore, methods that combine structural and functional neuroimaging data have been used to guide computer aided diagnosis techniques (Long et al, 2012; Ohtsuka et al, 2013; Prashanth et al, 2014; Rana et al, 2014; Salvatore et al, 2014; Weiner et al, 2013). More specifically, a technique called OPLS (orthogonal partial least squares to latent structures) is used to distinguish subjects with AD and MCI from healthy controls by combing MRI and CSF data (Westman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%